AN APPLICATION OF WAVELET THEORY TO ELECTROCARDIOGRAMS SINGULAR POINTS ANALYSIS - Trung, Nguyen Huu (Vietnam Journal of Science and Technology, 2012)
ABSTRACT In recent years, wavelet transform-based algorithms have been developed and successful in the signal processing in many areas since the wavelet transform is a useful and powerful tool for analysing signals in both transient and stationary intervals. In this paper, a report is made on an application of the mentioned capability of wavelet transform for grasping subtle changes and discontinuities in electrocardiogram (ECG) signals. From the signal processing point of view, it shows that the diagnostic of ECG signals is carried out by excluding any recognised abnormality as singular points or irregular structures. For analyzing purpose, wavelet footprints are characterized by scale-space vectors in a discrte model by discontinuing signals in piecewise polynominal. And a focus is made on applications of fetal ECG detection from maternal ECG.